Non-human primate studies for cardiomyocyte transplantation—ready for translation? - von Bibra, Constantin; Hinkel, Rabea (Frontiers in Pharmacology, 2024)
Non-human primates (NHP) are valuable models for late translational pre-clinical studies, often seen as a last step before clinical application. The unique similarity between NHPs and humans is often the subject of ethical concerns. However, it is precisely this analogy in anatomy, physiology and the immune system that narrows the translational gap to other animal models in the cardiovascular field. Cell and gene therapy approaches are two dominant strategies investigated in the research field of cardiac regeneration. Focusing on the cell therapy approach, several xeno-and allogenic cell transplantation studies with a translational motivation have been realized in macaque species. This is based on the pressing need for novel therapeutic options for heart failure patients. Stem cell-based remuscularization of the injured heart can be achieved via direct injection of cardiomyocytes (CM) or patch application. Both CM delivery approaches are in the late preclinical stage, and the first clinical trials have started. However, are we already ready for the clinical area? The present review concentrates on CM transplantation studies conducted in NHPs, discusses the main sources and discoveries, and provides a perspective about human translation.